Legal Certainty of Mineral Mining Permits as State Administrative Decisions: Between Regulation and Implementation - Sabri Guntur; Marlin; Syaiful Arpin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
One of the main challenges in Indonesia, particularly regarding the administration of mineral mining permits, is ensuring legal certainty—that is, having appropriate regulations and proper implementation. Because they constitute administrative decisions, mining permits often trigger disputes related to overlapping administrative authorities, procedural irregularities, and uneven policy enforcement. This study aims to examine the reflection of legal certainty in the regulation and administration of mineral mining permits, as well as to analyze the legal consequences arising from administrative inconsistencies in permitting practices. This study employs a normative legal methodology using legislative, conceptual, and case-based approaches. Legal materials are drawn from laws, court decisions, legal doctrines, and relevant academic articles on mining law and administrative law. The research findings indicate that although the laws and regulatory framework governing the issuance of mineral mining permits have established a formal design for certainty in administration, their implementation is consistently hindered by overlapping regulatory provisions, weak institutional coordination, and discretionary practices by government authorities. This creates uncertainty for investors, local communities, and the administration of state governance. Furthermore, this study demonstrates that mining permits, as Administrative Decisions, must be grounded in the principles of legality, transparency, accountability, and good governance to ensure legal protection and administrative justice. This study identified several key findings regarding the regulatory background of mineral resource management, related documents, and the involvement of third parties (stakeholders) in the permitting process. Theoretically, this study contributes to strengthening the discourse on the relationship between mining law and administrative law, with a critical focus on the importance of harmonizing regulatory policies and administrative implementation to provide legal certainty for the mineral mining sector in Indonesia.